Strategi Perencanaan Sumber Daya Manusia Dengan Metode Analisis SWOT Di PT X (Distributor Rokok Terbesar Di Indonesia) - Sapitri, Dian; Oktovian, Evan Nur; Mulyadi, Adi; Saputra, Agung Aditya (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2022)
This research aims to find out how the human resource planning strategy conducted by PT X Cigarette Distributor. This company is a cigarette distributor company and is the largest cigarette